Irrigation development, land tenure and climate shocks among farmers in the flood plain of Malawi: A pre-analysis plan and documentation for ethical approval by Institutional Review Board at NMBU - Sarah Tione; Stein Terje Holden; Samson Katengeza; Mesfin Tilahun (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2024)
This is a plan for the final component of the "Experiments for Development of Climate Smart Agriculture" (SMARTEX), which is a collaborative research and capacity-building program with School of Economics and Business (SEB) at NMBU, Ås, Norway and Lilongwe University of Agriculture and Natural Resources (LUANAR), Malawi, as the main partners. The Project builds on the long-term Collaboration between SEB-NMBU and LUANAR, including under NORHED I, the project Climate-Smart Natural Resource Management and Policy (CLISNARP). LUANAR has established its own PhD-program in Economics and is in strong need to further develop and strengthen its capacity to run this program. SEB-NMBU will contribute to this within the area of Behavioral and Experimental Economics, Climate Economics and Land Tenure and Property Markets. Especially the use of experimental methods will be applied to issues associated with finding climate smart solutions for sustainable intensification of agriculture in Malawi. Malawi is a very densely populated country that is highly dependent on agriculture. Food security is a very important policy objective for the country which faces severe climatic risks in terms of frequent droughts and floods. Researchers from SEB-NMBU will in collaboration with two postdocs and senior researchers from LUANAR carry out joint research within two specific areas. The first is to assess ways to transform the existing input subsidy program (FISP) to a program that more strongly stimulates Climate Smart Agriculture through reducing storage losses and land degradation. The second component will focus on land and water rights in relation to irrigation agriculture which holds potential but where institutional challenges need more attention. The project has a Malawian postdoc in each of these areas. These two postdocs received their PhDs from SEB-NMBU under CLISNARP (NORHED I). The project will help equip LUANAR to do more pro-active experimental research on these high priority policy areas. The project will establish a strong database through targeted surveys combined with field experiments that will serve as the basis for joint research by the postdocs in team with senior researchers from SEB-NMBU and LUANAR. The Pre-Analysis Plan presented here for ethical approval at HH-NMBU is for the second component of this project where Sarah Tione is the postdoc researcher. When the project started in 2021 neither NMBU or LUANAR had IRBs for ethical approval of research projects. However, as pre-registration and ethical approval have become the new international standard we have hereby prepared such a document for the remaining part of the project. The plan is to implement this fieldwork from early June 2024. The project will end July 31st, 2025 but the researchers involved expect to continue the analyses of the data for publication and dissemination purposes after that.
hdl:11250/3142674
Keywords: 330; Irrigation; flood shocks; impacts; irrigation group organization; performance; trust; social and economic preferences; welfare outcomes; land tenure; and land markets